Patterns of Dermatological manifestation in patients attending Pediatric outpatient department - Bhattarai, Arjun; Shrestha, Bandana; Timasina, Ravi Raj; KC, Nawaraj; Poudel, Shankar; Neupane, Saraswati (Journal of Gandaki Medical College-Nepal, 2020)
Background: Dermatological manifestations in children contribute to significant morbidity and psychological distress. Children with dermatological problems constitute a major bulk of the patients presenting to the Outpatient department. The study was conducted with an objective to find out the pattern of skin disease among the various pediatric age group.Method: We analyzed epidemiological data of 612 patients, aged 1 months to 15 years, who were referred to the Dermatology outpatient from the Pediatric outpatient between 2nd Baisakh 2075 to 31 Chaitra 2076. Demographic data and the frequency of the various diagnoses in various age groups were studied.Result: The most common category of diagnosis was infection in 35.78%, followed by allergic reaction in 33.50% and infestations in 14.22%, other dermatosis in 13.07%, while multiple diagnosis was found in 3.43%. Among all diagnostic groups, Scabies was the most common (14.22%) followed by Urticaria (11.92%).Conclusion: Comparison of the common dermatosis with the age group showed a strongly significant effect on occurrence of common dermatosis. Their incidence can be brought down by improving nutrition and personal hygiene of children. Health and wellness of school going children reflects the health status of a community. Our study provides a preliminary baseline data for future epidemiological and clinical research.